Das Dorf am Ende der Welt - Barahona, Sebastián (Yeti Film, 2005)
Villa las Estrellas: a couple of houses, a supermarket, a school. All in the South Pole. When the penguins migrate, the town has only 48 inhabitants. Children have more recreation than classes and look forward to the goodies that will arrive at the supermarket. Villa las estrellas is a documentary that observes the daily life of this Antarctic people, without interventions, a unique approach to the way they live in this place --